A spontaneous missense mutation in the chromodomain helicase DNA‐binding protein 8 (CHD8) gene: a novel association with congenital myasthenic syndrome. (7th May 2020) - Lee, C. Y.; Petkova, M.; Morales‐Gonzalez, S.; Gimber, N.; Schmoranzer, J.; Meisel, A.; Böhmerle, W.; Stenzel, W.; Schuelke, M.; Schwarz, J. M.
Abstract : Aims: Congenital myasthenic syndromes (CMS) are characterized by muscle weakness, ptosis and episodic apnoea. Mutations affect integral protein components of the neuromuscular junction (NMJ). Here we searched for the genetic basis of CMS in female monozygotic twins. Methods: We employed whole‐exome sequencing for mutation detection and Sanger sequencing for segregation analysis. Immunohistology was done with antibodies against CHD8, rapsyn, β‐catenin (βCAT) and golgin on fi‐bro‐blasts, human and mouse muscle. We recorded superresolution images of the NMJ using 3D‐structured illumination microscopy. Results: We discovered a spontaneous missense mutation in CHD8 [chr14:g.21, 884, 051G>A, GRCh37.p11 | c.1732C>T, NM_00117062 | p.(R578C)], the gene encoding chromodomain helicase DNA‐binding protein 8. This is the first missense mutation affecting Duplin, the short 110 kDa isoform of CHD8. It is known that CHD8/Duplin negatively regulates βCAT signalling in the WNT pathway and plays a role in chromatin remodelling. Inactivating CHD8 mutations are associated with autism spectrum disorder and intellectual disability in combination with facial dysmorphism, overgrowth and macrocephalus. No muscle‐specific phenotype has been reported to date. Co‐immunostaining with rapsyn on human and mouse muscle revealed a strong presence of CHD8 at the NMJ being located towards the sarcoplasmic side of the rapsyn cluster, where it co‐localizes with βCAT. Conclusion: We hypothesize CHD8 to have a role in the maintenance of the structural integrity and function of the NMJ. Both patients benefited from treatment with 3, 4‐diaminopyridine, a reversible blocker of voltage‐gated potassium channels at the nerve terminal that prolongs the action potential and increases acetylcholine release.